2017
DOI: 10.2147/ijn.s137245
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid-functionalized polyethylenimine superparamagnetic iron oxide nanoparticles as theranostic agents for magnetic resonance imaging and PD-L1 siRNA delivery for gastric cancer

Abstract: Programmed death ligand-1 (PD-L1), which is highly expressed in gastric cancers, interacts with programmed death-1 (PD-1) on T cells and is involved in T-cell immune resistance. To increase the therapeutic safety and accuracy of PD-1/PD-L1 blockade, RNA interference through targeted gene delivery was performed in our study. We developed folic acid (FA)- and disulfide (SS)–polyethylene glycol (PEG)-conjugated polyethylenimine (PEI) complexed with superparamagnetic iron oxide Fe 3 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…Two other types of inorganic delivery vehicles, namely, silica-based ( Niut et al, 2012 ) and superparamagnetic iron oxide ( Taratula et al, 2011 ; Luo et al, 2017 ) nanoparticles have been proposed as nucleic acid carriers due to their enhanced loading capacity and the possibility to monitor biodistribution, respectively. These materials cannot innately promote endosomal disruption and need additional chemical modifications to tune their endosomal escape capabilities.…”
Section: Endosomal Escapementioning
confidence: 99%
“…Two other types of inorganic delivery vehicles, namely, silica-based ( Niut et al, 2012 ) and superparamagnetic iron oxide ( Taratula et al, 2011 ; Luo et al, 2017 ) nanoparticles have been proposed as nucleic acid carriers due to their enhanced loading capacity and the possibility to monitor biodistribution, respectively. These materials cannot innately promote endosomal disruption and need additional chemical modifications to tune their endosomal escape capabilities.…”
Section: Endosomal Escapementioning
confidence: 99%
“…13,14 Previous studies showed that simultaneously delivering chemotherapeutic drugs and siRNA via a single targeted vector was more effective in treating some cancers than sequential administration of two separate vectors with one drug in each. 15 This finding indicates that simultaneous delivery of chemotherapeutic drugs and suitable amount of siRNA into the same tumor plays an important role in the cancer treatments. 16 Emerging evidence has proposed that human homeobox protein (Nanog) is a excellent target in cancer therapy owing to its regulation of cancer cell proliferation, metastasis and apoptosis.…”
Section: Introductionmentioning
confidence: 96%
“…PEI, which is used as a coating in this study, is a cationic polymer that binds to the anionic cell membrane phospholipids and enables uptake. [36] It can be used as a gene delivery vehicle [37], a contrast agent for imaging [38,39], and a biosensor for glutamate detection. [40] Chithrani et al evaluated the size and shape dependence of AuNPs' uptake into mammalian cells, and observed the highest uptake and radiosensitization with approximately 50 nm compared to the 14 nm and 70 nm.…”
Section: Discussionmentioning
confidence: 99%